Anti Hepatotoxic Effect of Cow Urine Distillate Against Paracetamol Induced Hepatic Damage in Rats - Gururaja, M.P.; Joshi, A.B.; Joshi, Himanshu (Asian Journal of Chemistry, 2010)
The effect of cow urine distillate was studied on paracetamol induced hepatic injury in albino rats. The hepatotoxicity was induced in rats by oral administration of paracetamol (2 g/kg). The effect of cow urine distillate were studied in three dose level and compared with that of standard drug silymarin (100 mg/kg, po). The cow urine distillate produced dose dependent significant (p < 0.05) lowering of the elevated SGOT, SGPT, ALP, GGT and total bilirubin levels when compared with the toxic control. The results were comparable with the standard drug silymarin.